4D Near-Field Source Localization Using Cumulant. (23rd May 2007) - Liang Liang, Junli Junli; Yang Yang, Shuyuan Shuyuan; Zhang Zhang, Junying Junying; Gao Gao, Li Li; Zhao Zhao, Feng Feng
Abstract : This paper proposes a new cumulant-based algorithm to jointly estimate four-dimensional (4D) source parameters of multiple near-field narrowband sources. Firstly, this approach proposes a new cross-array, and constructs five high-dimensional Toeplitz matrices using the fourth-order cumulants of some properly chosen sensor outputs; secondly, it forms a parallel factor (PARAFAC) model in the cumulant domain using these matrices, and analyzes the unique low-rank decomposition of this model; thirdly, it jointly estimates the frequency, two-dimensional (2D) directions-of-arrival (DOAs), and range of each near-field source from the matrices via the low-rank three-way array (TWA) decomposition. In comparison with some available methods, the proposed algorithm, which efficiently makes use of the array aperture, can localizeN − 3 sources usingN sensors. In addition, it requires neither pairing parameters nor multidimensional search. Simulation results are presented to validate the performance of the proposed method.